Transforming Students’ Literacy through Metaverse-Based Ethnolinguistic Folklore of Kajao Laliddong and Bugis-Bone Cultural Values - Ayunita; Idris; Muhammad Asdar; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Andi Srimularahmah; Andi Nurannisa (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2026)
Junior high school students’ literacy skills remain relatively low due to the limited use of innovative learning media and the minimal integration of local cultural values into Indonesian language learning. This study aimed to analyze the effect of implementing Metaverse-based ethnolinguistic folklore of Kajao Laliddong on improving students’ literacy skills. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The participants consisted of 60 seventh-grade students at SMPN 2 Libureng, divided into an experimental class and a control class with 30 students. Data were collected through pre-tests and post-tests, observations, as well as student and teacher response questionnaires. Data analysis was conducted using descriptive and inferential statistics, including normality tests, the Mann–Whitney U test, and N-gain analysis. The findings revealed that the experimental class mean score increased from 43.23 to 74.14 in the post-test, while the control class improved from 33.79 to 67.07. The experimental class achieved an N-gain score of 0.67 (moderate), which was higher than the control class score of 0.23 (low). Statistical analysis indicated that the calculated t-value (6.836) exceeded the t-table value (2.001), demonstrating a significant difference between the two groups. Student responses toward the use of Metaverse-based media reached an average score of 89.2% in the very good category, while teacher responses reached 90.1%, also categorized as very good. The study concludes that Metaverse-based ethnolinguistic folklore of Kajao Laliddong effectively improves students’ literacy skills while fostering an interactive, contextual, and culturally responsive learning environment.